Amino acid metabolism: challenges and opportunities for the therapeutic treatment of leukemia and lymphoma. Issue 7 (4th July 2022) - Liao, Peiyun; Chang, Ning; Xu, Binyan; Qiu, Yingqi; Wang, Sheng; Zhou, Lijuan; He, Yanjie; Xie, Xiaoling; Li, Yuhua
Abstract: Leukemia and lymphoma—the most common hematological malignant diseases—are often accompanied by complications such as drug resistance, refractory diseases and relapse. Amino acids (AAs) are important energy sources for malignant cells. Tumor‐mediated AA metabolism is associated with the immunosuppressive properties of the tumor microenvironment, thereby assisting malignant cells to evade immune surveillance. Targeting abnormal AA metabolism in the tumor microenvironment may be an effective therapeutic approach to address the therapeutic challenges of leukemia and lymphoma. Here, we review the effects of glutamine, arginine and tryptophan metabolism on tumorigenesis and immunomodulation, and define the differences between tumor cells and immune effector cells. We also comment on treatments targeting these AA metabolism pathways in lymphoma and leukemia and discuss how these treatments have profound adverse effects on tumor cells, but leave the immune cells unaffected or mildly affected. Abstract : In this article, we discuss the abnormal amino acid pathways in leukemia and lymphoma and how they associate with immune escape. In addition, we discuss emerging therapeutic targets, which may provide a new direction on immunotherapy for leukemia.